Nowe spojrzenie na relacje z odbiorcami a organizacja ucząca się - Kubacka-Góral, Krystyna (Customer relationship - a new approach in the context of the learning organization, 2006)
The aim of the paper is to present a modern approach to Customer Relationship Management. The implementation of the idea of consumption chain described in the paper constitutes an opportunity to Polish companies to attain competitive advantage. In the paper the following issues are discussed: consumption chain as a factor of competitive advantage, organizational learning process and the role of intellectual capital and information technology in contemporary company.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1137, s. 85-93